1992
DOI: 10.1016/s0886-3350(13)80903-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hyaluronic acid and hyaluronic acid binding sites on human corneal endothelium

Abstract: A highly specific hyaluronic acid (HA) recognizing protein (HABR) was used to study whether the human corneal endothelium is covered by HA and to quantify the amount. Tritiated high molecular weight HA was used to determine the capacity of the human endothelium to bind exogenous HA. Human corneas were obtained from keratoconus patients having corneal transplantation and from postmortem eyes. The corneas were immersed in a 4% formaldehyde solution containing 1% cetylpyridine chloride for histochemistry, frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Hyaluronic acid has binding sites on the endothelium and may provide mechanical and chemical protection during surgery. 14 The endothelial cell loss in this study is comparable to that in other studies. 4,[15][16][17] The aim of this study was to compare endothelial damage after standard cataract surgery and MICS.…”
Section: Discussionsupporting
confidence: 89%
“…Hyaluronic acid has binding sites on the endothelium and may provide mechanical and chemical protection during surgery. 14 The endothelial cell loss in this study is comparable to that in other studies. 4,[15][16][17] The aim of this study was to compare endothelial damage after standard cataract surgery and MICS.…”
Section: Discussionsupporting
confidence: 89%
“…In the posterior segment of the eye, HA has been detected in the vitreous humor, neurosensory retina, retinal pigmented epithelium, Bruch’s membrane and choroid ( Clark et al, 2011 ). In the anterior segment of normal eyes, HA has been detected in the aqueous humor, trabecular meshwork, iris stroma, lens capsule, corneal endothelium, conjunctival epithelium and limbal epithelium ( Figure 4 ) ( Härfstrand et al, 1992 ; Gong et al, 1994 ; Lerner et al, 1998 ; Gartaganis et al, 2001 ; Gesteira et al, 2017 ). Although studies have shown that the biological function of HA is dictated by its molecular weight, the molecular size of HA in these tissues have not been determined.…”
Section: Hyaluronanmentioning
confidence: 99%
“…Formation of HA deposits has been described following excimer laser surgery , alkali wounding to the cornea , and mechanical wounding (knife incision) (Molander et al 1993a(Molander et al & 1993b. HA is classified among the proteoglycans, and it is not found in the normal or uninjured corneal stroma (Madsen et al 1989;Lutjen-Drecoll et al 1990;Härfstrand et al 1992). Several investigators have described the HA production in the chick embryo during a period of corneal stromal swelling and invasion by mesenchymal cells (Toole & Trelstad 1971;Trelstad et al 1974;Hart 1978;Toole 1982).…”
mentioning
confidence: 99%